Penerapan Prinsip-Prinsip Mengajar Oleh Guru PAI di SMP N 1 Singingi Hilir Provinsi Riau - Raul Maldini; Salmi Wati; Junaidi Junaidi; Yelfi Dewi (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The background of this research is that students feel that the methods used by the teacher are less varied so that students feel bored, then the teacher rarely connects learning material with student interests. In addition, the teacher explains more about the lesson than the students. The teacher only conveys material to students, while students have different abilities in understanding the material. The research objective was to find out how the principles of motivation, activity and individuality were applied by PAI teachers in class 2A at SMP N 1 Singingi Hilir. This study uses a qualitative approach. With data collection techniques through observation and interviews. The key informants were PAI teachers and the supporting informants were class 2A students. Data analysis in this study was done by reducing data, displaying data, and then drawing conclusions. Based on the results of the study it was found: (1) Principles of motivation: teachers rarely choose teaching materials that suit students' interests, teachers rarely use teaching methods and techniques that students like, teachers rarely make corrections as soon as possible to student work and share the results with students. (2) The principle of activity: teachers rarely use multi-methods and multi-media in learning (3) The principle of individuality: teachers rarely use methods that are able to serve the needs of students according to their characteristics, then teachers also rarely use media in learning, then teachers rarely determine the right treatment for the students concerned